2014
DOI: 10.1155/2014/726590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nrf2 Deficiency on Bone Microarchitecture in an Experimental Model of Osteoporosis

Abstract: Objective. Redox imbalance contributes to bone fragility. We have evaluated the in vivo role of nuclear factor erythroid derived 2-related factor-2 (Nrf2), an important regulator of cellular responses to oxidative stress, in bone metabolism using a model of postmenopausal osteoporosis. Methods. Ovariectomy was performed in both wild-type and mice deficient in Nrf2 (Nrf2−/−). Bone microarchitecture was analyzed by μCT. Serum markers of bone metabolism were also measured. Reactive oxygen species production was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 34 publications
5
68
0
Order By: Relevance
“…Previous studies with Nrf2 knockout (KO) mice have shown sexual dimorphism in the skeletal phenotype of Nrf2 KO mice 1,9,23,24 . Female Nrf2 KO mice always show lower bone mass than the female WT mice 9,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with Nrf2 knockout (KO) mice have shown sexual dimorphism in the skeletal phenotype of Nrf2 KO mice 1,9,23,24 . Female Nrf2 KO mice always show lower bone mass than the female WT mice 9,24 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that reactive oxygen species (ROS) acts as intracellular signaling molecules to regulate osteoclast differentiation, and the Keap1/Nrf2 axis plays a role in osteoclast differentiation by regulating intracellular ROS signaling 8 . More studies revealed that deletion of Nrf2 reduces skeletal mechanical properties 1,9 , decreases load-driven bone formation 1 , impairs fracture healing in mice 10 , induces oxidative stress and promotes RANKL-induced osteoclast differentiation 11 . So Nrf2 is considered as playing an important role in the regulation of bone homeostasis in bone cells 12 .…”
mentioning
confidence: 99%
“…Black bear parathyroid hormone activates cAMP, mitigates apoptosis in osteoblast cultures and increases trabecular bone volume (247); hence, the anabolic effects of bear parathyroid hormone might also prevent disuse osteoporosis. In addition, NRF2 was reported to have a role in bone microarchitecture in a mouse model of osteoporosis (248) and inhibits receptor activator of NF-B ligand (RANKL)-mediated osteoclastogenesis in osteolysis-induced mice (249). Given the fact that increased NRF2 expression plays a major part in the antioxidant defences that are required for hibernation success in ground squirrels (250), the potential role of NRF2 in maintaining skeletal mass in hibernating bears warrants investigation.…”
Section: Major Differences Exist In Levels Of Serum Biomarkers Of Micmentioning
confidence: 99%
“…vasomotor complains, CVD, osteoporosis, cognitive impairment and urogenital dystrophy, etc.) [8,[10][11][12][13][14][15][16][17] grouped together in the "menopausal syndrome".…”
Section: Introductionmentioning
confidence: 99%